Application of quantum chemical descriptors in QSAR analysis of curcumin derivatives as ethoxyresorufin o-dealkylation inhibitor - Sudarmanto, B.S. Ari; Oetari, R. A. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Quantitative Structure-Activity Relationship (QSAR) have established 26 curcumin derivatives to correlate and predict ethoxyresorufin Odeethylation (EROD) inhibitory activity. The AM1 semiempirical quantum mechanic method was applied in geometry optimization and descriptor calculation. Genetic Algoritm combined with Multiple Linear Regression Analysis (GA-MLRA) technique was applied to select the descriptors and to generate the equation that relate the structural features to the biological activity. The result of GA-MLRA showed that quantum chemical descriptors QSAR had good statistical fits. Energy level of the lowest unoccupied molecular orbital, logP, momen dipole, and nett charge of C1, C6 and C9 atoms play an important role in EROD inhibition.Key words : QSAR, quantum-chemical descriptor, curcumin derivatives, EROD.